A distribution-free approach for selecting better treatment through an ethical allocation. Issue 2 (3rd April 2019) - Das, Radhakanta
ABSTRACT: The present article provides a statistical inference on comparative performances of two treatments in a clinical trial under a two-stage adaptive allocation design. Suppose a fixed number (2 m + n, say) of subjects are available for treatment by any of the two competing treatments, say, A and B for a particular ailment. As per the proposed allocation design, 2 m incoming subjects are randomised equally between A and B at the first stage. Then, at the second stage, the remaining n subjects are exclusively assigned to the treatment which has higher observed median response evaluated in the first stage. Under such an ethical allocation design we decide on the better treatment through an asymptotically distribution-free test procedure. The related asymptotic results are also studied.